Analyzing accusation patterns between Hamas and Israel during the Al-Aqsa flood operation - Alaeddin A. Banikalef; Nisreen N. Al-Khawaldeh (Humanities & Social Sciences Communications)
Abstract This study investigates the accusation strategies utilized by both Israel and Hamas during the Al Aqsa Flood operation. Through a comprehensive analysis of twenty-four speeches delivered by Abu-Obieda, the military spokesman of Hamas, and Rear Admiral Daniel Hagari, the military spokesperson of the Israel Defense Forces (IDF), this research identifies key accusation patterns and examines the application of Aristotle’s modes of persuasion (ethos, pathos, and logos) alongside word frequency analysis. The Results reveal that while Abu-Obieda leverages emotional and ethical appeals supported by tangible evidence (e.g., videos, eyewitness accounts), Hagari adopts a more strategically balanced approach, combining emotional, logical, and ethical arguments to shape public perception. This study introduced a rigorously defined framework for categorizing accusations in conflict discourse, contributing to both rhetorical theory and conflict communication strategies. Future research should further explore the evolving dynamics of accusation strategies, media influence, and public opinion in conflict zones to improve communication and promote reconciliation efforts.